Comprehensive detection of CRLF2 alterations in acute lymphoblastic leukemia: a rapid and accurate novel approach - Gil, José Vicente; Miralles, Alberto; de las Heras, Sandra; Such, Esperanza; Avetisyan, Gayane; Díaz-González, Álvaro; Santiago, Marta; Fuentes, Carolina; Fernández, José María; Lloret, Pilar; Navarro, Irene; Montesinos, Pau; et al. (Frontiers in Molecular Biosciences, 2024)
Introduction: Acute lymphoblastic leukemia (ALL) is a prevalent childhood cancer with high cure rate, but poses a significant medical challenge in adults and relapsed patients. Philadelphia-like acute lymphoblastic leukemia (Ph-like ALL) is a high-risk subtype, with approximately half of cases characterized by CRLF2 overexpression and frequent concomitant IKZF1 deletions. Methods: To address the need for efficient, rapid, and cost-effective detection of CRLF2 alterations, we developed a novel RT-qPCR technique combining SYBR Green and highresolution melting analysis on a single plate. Results: The method successfully identified CRLF2 expression, P2RY8::CRLF2 fusions, and CRLF2 and JAK2 variants, achieving a 100% sensitivity and specificity. Application of this method across 61 samples revealed that 24.59% exhibited CRLF2 overexpression, predominantly driven by IGH::CRLF2 (73.33%). High Resolution Melting analysis unveiled concurrent CRLF2 or JAK2 variants in 8.19% of samples, as well as a dynamic nature of CRLF2 alterations during disease progression. Discussion: Overall, this approach provides an accurate identification of CRLF2 alterations, enabling improved diagnostic and facilitating therapeutic decision-making.